2007
DOI: 10.1111/j.1529-8817.2007.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific physiological response of dinoflagellates to quantified small‐scale turbulence1

Abstract: Turbulence has been shown to alter different aspects of the physiology of some dinoflagellates. The response appears to be species-specific and dependent on the experimental design and setup used to generate small-scale turbulence. We examined the variability of the response of three dinoflagellate species to the turbulence, following the same experimental design used by Berdalet (1992) on Akashiwo sanguinea (Hirasaka) Ge. Hansen et Moestrup (=Gymnodinium nelsonii G. W. Martin). In all experiments, turbulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
86
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 56 publications
(150 reference statements)
13
86
1
1
Order By: Relevance
“…A scheme of the setup used to perform × estimations can be found in Fig. 1 of Berdalet et al (2007). A complete description of the calculations was provided by Guadayol et al (2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A scheme of the setup used to perform × estimations can be found in Fig. 1 of Berdalet et al (2007). A complete description of the calculations was provided by Guadayol et al (2009).…”
Section: Methodsmentioning
confidence: 99%
“…To address this question, we collected field samples during 3 distinct and temporally separated phases of a phytoplankton spring bloom, characterised by the presence of Prorocentrum micans, Scrippsiella trochoidea and the toxic Alexandrium minutum, as well as the parasite Parvilucifera sinerae, which has the capacity to infect the latter 2 dinoflagellate species. We then subjected the samples to laboratory-generated turbulence (using the same experimental setup as in previous studies on turbulence-dinoflagellate interactions; Berdalet et al 2007, Bolli et al 2007, Llaveria et al 2009) or kept them unperturbed. We compared the 2 treatments in terms of dinoflagellate cell abundances and data on the infectivity by P. sinerae.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…Dinoflagellates appear as the group showing a diversity of particular responses to this, not well understood yet, environmental factor. The available data indicate that the direct effect of turbulence is species-specific and dependent on the experimental conditions (Berdalet and Estrada, 1993;Berdalet et al, 2007), although direct comparison between studies is not straightforward (Peters and Marrasé, 2000). Some studies have found positive (or indifferent) biological responses (Berdalet and Estrada, 1993;Havskum et al, 2005;Havskum and Hansen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cages were slowly moved up and down three times a day to promote the exchange of medium and dissolved compounds (including allelochemicals) between the two compartments. Experiments were terminated after 24, 48, 72 and 96 h; the first 24 h was considered to be an acclimation phase because dinoflagellates are sensitive to mixing (Berdalet et al, 2007) and often show a prolonged lag-phase after cell culture transfer.…”
Section: Experimental Designmentioning
confidence: 99%